Empowering Mosque Youth in Banana Cultivation, Processing, and Marketing of Banana-Based Snacks - Ibrahim, Mardiana; AR, Sri Hajriani; Ahmad, Fadillah (Perpustakaan dan Penerbitan Unismuh Makassar, 2024)
This research aims to empower mosque youth in Parangbanoa Village, Palangga District, Gowa Regency, in optimizing the use of existing natural resources, especially banana trees, through cultivating, processing and marketing banana-based snacks. Parangbanoa Village has natural potential in the form of abundant banana plants, but it has not been utilized optimally by the community, especially the mosque youth, in creating products of economic value. For this reason, training and mentoring activities are carried out involving mosque youth in the process of cultivating good bananas, processing bananas into snacks such as banana chips, banana cake and banana pudding, as well as effective marketing strategies to increase product competitiveness. The method used in this research is Mentoring and Empowering through a Participatory Action Research (PAR) approach, where mosque youth are directly involved in every stage of the activity. The results of the activity show that mosque youth are increasingly skilled in processing bananas into various snack products which have good market potential. Apart from that, they also gain new knowledge about marketing techniques that can be used to introduce their products to a wider market. Through this program, it is hoped that mosque youth in Parangbanoa Village can improve the family economy, create new jobs, and make bananas a superior commodity that can be processed into high-value products.